The Kali Samin Hydroelectric Power Plant as an instrument of social change and an arena of power contestation in Vorstenlanden, 1933–1938 - Andrik Sulistiyawan (PT Bina Perfidia Akademia, 2026)
Studies on colonial electrification have been widely conducted. However, the relationship between the Kali Samin Hydroelectric Power Plant, social change, and power contestation in Vorstenlanden has received limited integrated historical analysis. This study aims to examine the Kali Samin Hydroelectric Power Plant as an instrument of social change and an arena of power contestation during the reign of Mangkunegara VII. The research employed the historical method, consisting of heuristics, source criticism, interpretation, and historiography, using colonial newspapers as primary sources and books, journal articles, and a thesis as secondary sources. The findings reveal that the Kali Samin Hydroelectric Power Plant not only expanded electricity supply but also stimulated economic modernization, tourism, and bureaucratic development through collaboration among the Mangkunegaran Principality, the colonial government, electricity companies, and technical experts. This study highlights energy infrastructure as both an instrument of social transformation and a medium of negotiated power in the modernization of Vorstenlanden. Abstrak Pembangunan infrastruktur ketenagalistrikan pada masa kolonial telah banyak dikaji. Namun, hubungan antara pembangunan Pembangkit Listrik Tenaga Air (PLTA) Kali Samin, perubahan sosial, dan kontestasi kekuasaan di Vorstenlanden masih belum dianalisis secara terpadu. Penelitian ini bertujuan menganalisis pembangunan PLTA Kali Samin sebagai instrumen perubahan sosial sekaligus arena kontestasi kekuasaan pada masa pemerintahan Mangkunegara VII. Penelitian menggunakan metode sejarah yang meliputi tahapan heuristik, kritik sumber, interpretasi, dan historiografi dengan memanfaatkan surat kabar kolonial sebagai sumber primer serta buku, artikel jurnal, dan tesis sebagai sumber sekunder. Hasil penelitian menunjukkan bahwa PLTA Kali Samin tidak hanya meningkatkan penyediaan energi, tetapi juga mendorong modernisasi ekonomi, pariwisata, dan birokrasi melalui kolaborasi antara Praja Mangkunegaran, pemerintah kolonial, perusahaan listrik, dan tenaga ahli. Penelitian ini menegaskan bahwa infrastruktur energi berfungsi sebagai instrumen perubahan sosial sekaligus medium negosiasi kekuasaan dalam proses modernisasi Vorstenlanden.